A computational simulation model for assessing social performance of BIM implementations in construction projects. Issue 2 (7th April 2021) - Zoghi, Milad; Lee, Donghoon; Kim, Sungjin
Abstract: The construction industry has been adopting building information modeling (BIM) to enhance project and social performance. However, it is difficult to address and assess how integrating BIM into construction can support improving social performance. Thus, this study developed a system dynamics (SD) model to evaluate the social performance of BIM-integrated construction management. The proposed model aims to demonstrate the dynamic behavior of social indicators in construction and their interrelationships. The developed model was simulated under the different scenarios by different levels of BIM implementations. As a result, levels 2 and 3 of BIM implementation can enhance social performance by 26% and 45%, respectively. This study is limited to develop the SD model and assessing the performance without the vaildation through case study. However, this study can contribute to developing the simulation model to address how the BIM can affect the social performance in the construction industry. Graphical Abstract: